Continuous meteorological surface measurement during POLARSTERN cruises (ARK-IX/2 et seq) - Holger Schmithüsen (PANGAEA, 2026)
The meteorological observatory Polarstern continuously acquires meteorological parameters during times of ship operation. Measurements are taken on various locations on the vessel, instrument heights above sea level are given below. All data is quality controlled. Measurements are checked daily on board by the operator and again prior to publication. Knowingly affected or erroneous data is removed. New data will be added regularly.